Anti-CD2 Antibody-Coated Nanoparticles Containing IL-2 Induce NK Cells That Protect Lupus Mice via a TGF-β-Dependent Mechanism - Horwitz, David A.; Liu, Aijing; Bickerton, Sean; Castaldo, Giuseppe; Matarese, Giuseppe; Fahmy, Tarek M.; La Cava, Antonio (Frontiers in Immunology, 2020)
-